2020
DOI: 10.1128/jvi.01644-19
|View full text |Cite
|
Sign up to set email alerts
|

Functional Perturbation of Mucosal Group 3 Innate Lymphoid and Natural Killer Cells in Simian-Human Immunodeficiency Virus/Simian Immunodeficiency Virus-Infected Infant Rhesus Macaques

Abstract: Mother-to-child transmission of human immunodeficiency virus type 1 (HIV-1) via breastfeeding is responsible for nearly half of new infections of children with HIV. Although innate lymphoid cells (ILC) and natural killer (NK) cells are found throughout the oral mucosae, the effects of HIV/simian-human immunodeficiency virus (SHIV) in these tissues are largely unknown. To better understand the mechanics of postnatal transmission, we performed a comprehensive study of simian immunodeficiency virus (SIV)/SHIV-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…The infection altered the trafficking and chemokine receptors in ILC3s, reducing the expression of a4b7 integrin in colonic ILC3s and consequently minimizing IL-22 secretion in colon and oral mucosa. The aforementioned study corroborated the premise that the lentivirus infection could have significant effects on the frequency, phenotype, and function of innate cells in the oral and gut mucosa such as the reduction of ILC3 IL-22 + which might be particularly relevant in infants infected through breastfeeding, because their immune system is not fully functional (62). Importantly, it has recently been demonstrated that NKp44 + ILCs play a protective role in the progression of the disease, as their higher frequency in the mucosa was associated with delayed SIV acquisition and decreased viremia in vaccinated macaques (63), thus confirming previous published data (64).…”
Section: The Repercussion Of Blood or Systemic Infections In Ilc3 Population Immunodeficiency Viruses Reduce Ilc3s In Infected Subjectssupporting
confidence: 74%
“…The infection altered the trafficking and chemokine receptors in ILC3s, reducing the expression of a4b7 integrin in colonic ILC3s and consequently minimizing IL-22 secretion in colon and oral mucosa. The aforementioned study corroborated the premise that the lentivirus infection could have significant effects on the frequency, phenotype, and function of innate cells in the oral and gut mucosa such as the reduction of ILC3 IL-22 + which might be particularly relevant in infants infected through breastfeeding, because their immune system is not fully functional (62). Importantly, it has recently been demonstrated that NKp44 + ILCs play a protective role in the progression of the disease, as their higher frequency in the mucosa was associated with delayed SIV acquisition and decreased viremia in vaccinated macaques (63), thus confirming previous published data (64).…”
Section: The Repercussion Of Blood or Systemic Infections In Ilc3 Population Immunodeficiency Viruses Reduce Ilc3s In Infected Subjectssupporting
confidence: 74%
“…Although not yet measured in humans, SIV studies have shown depletion of ILC3s in the infant NHP gut (Hueber et al, 2020), as well as depletion and phenotypic skewing of NKp44 + ILCs during acute infection in adult gut (Li et al, 2014), and suggested protective qualities of ILC3s in adenovirus-SIV vaccination and With the advent of next-generation sequencing and steady improvements in low-input and single-cell profiling technologies, highcontent measurements of gene expression, protein expression, open chromatin, and other cellular features are becoming increasingly accessible and affordable substantial insights into disease biology in heterogeneous tissue environments (Hartmann and Bendall, 2020;Shema et al, 2019;Stubbington et al, 2017). Critically, many of these assays can be used to study rare cell types from low-input samples like tissue biopsies, fine-needle aspirates, and small amounts of blood.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…OPEN ACCESS mother-to-child transmission (Hueber et al, 2020;Rahman et al, 2019). Groups 1 and 3 ILCs present in the GI tract during SIV infection potentially contribute to pro-inflammatory responses by producing higher levels of IFN-g, tumor necrosis factor (TNF)-a, and IL-22 during the breakdown of the epithelium (Cogswell et al, 2020); however, when these pro-inflammatory ILCs arise is unknown.…”
Section: Llmentioning
confidence: 99%
“…In response to mouse enteric rotavirus infections, epithelial IL-1a induced ILC3-derived IL-22 which synergized with epithelial IFN-l, promoting the induction of antiviral gene expression in intestinal epithelial cells, limiting viral replication and tissue damage (Figure 6C) (220). While ILC3s can promote antiviral immunity, they experience cytokine-dependent depletion in the intestinal tract of HIV + human and SIV + non-human primates, altering epithelial permeability and homeostasis (221)(222)(223). Collectively, ILCs promote intestinal barrier defense against enteric bacterial, fungal, and viral infections by exerting cytokine or cell contactdependent effects on intestinal epithelial cells.…”
Section: Gastrointestinal Infectionmentioning
confidence: 99%